2013
DOI: 10.1371/journal.pone.0082718
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Attrition and Immunological Failure in HIV-1 Patients on Highly Active Antiretroviral Therapy from Different Healthcare Settings in Mozambique

Abstract: In Mozambique, the evaluation of retention in HIV care and ART programmes is limited. To assess rate and predictors of attrition (no retention in care) and HAART effectiveness in HIV-1 infected patients who pay for medication and laboratory testing in Mozambique, we conducted a multicenter survey of HIV-1-infected patients who started HAART during 2002–2006. Cox proportional hazard models were used to assess risk of attrition and of therapy failure. Overall, 142 patients from 16 healthcare centers located in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
3
19
2
Order By: Relevance
“…Findings of no association were similar with respect to age, gender, tuberculosis, and treatment interruption. In the Mozambique study, the CD4 cell count association was similar to findings form the current study [ 43 ]. The fact that there was no association between adherence to antiretroviral medication refill and immunological treatment failure was a surprising finding.…”
Section: Discussionsupporting
confidence: 88%
“…Findings of no association were similar with respect to age, gender, tuberculosis, and treatment interruption. In the Mozambique study, the CD4 cell count association was similar to findings form the current study [ 43 ]. The fact that there was no association between adherence to antiretroviral medication refill and immunological treatment failure was a surprising finding.…”
Section: Discussionsupporting
confidence: 88%
“…This incidence rate is relatively low as compared to the incidence rate reported by different studies in Ethiopia and abroad [ 10 , 14 , 15 ]. A study from Mozambique reported that rate of immunologic failure was 17.2 (95% CI: 12.6–22.9) per 100 person-years of follow-up [ 16 ]. Another study from Thailand showed that 4.3%, 10.7%, and 4.9% met the criteria of virological failure, immunological failure, and clinical failure, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The study on fee based ART program in Mozambique showed that, the risk of failure was higher among patients with a high baseline CD 4 cell count and low baseline viral load. The result reflected that these groups of patients might have low adherence level due to the lower risk of developing opportunistic infections [ 26 , 27 ]. Contrary to these findings, a low rate of immunologic treatment failure was reported from a study in India [ 28 ].…”
Section: Introductionmentioning
confidence: 99%